The effect of migration on careers of natives: Evidence from long-term care - Peter Haan; Izabela Wnuk (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
This paper examines the effect of increasing foreign staffing on the labor market outcomes of native workers in the German long-term care sector. Using administrative social security data covering the universe of long-term care workers and policy-induced exogenous variation, we find that increased foreign staffing reduces labor shortages but has diverging implications for the careers of native workers in the sector. While it causes a transition of those currently employed to jobs with better working conditions, higher wages, and non-manual tasks, it simultaneously diminishes re-employment prospects for the unemployed natives with LTC experience.
Keywords: J61; I11; 330; immigration; shift-share instrument; long-term care; EU Enlargement